The Impact of Managerial Communications on Organizational Change Management: Jordan Customs as a Case Study - Hussain, Bashar Walid; Qawasmeh, Farid Mohammad (Journal of Economic, Administrative and Legal Sciences, 2020)
This study aims to identify the impact of managerial communications on organizational change management in Jordan Customs Department. To achieve the study objective which uses analytical and descriptive type of a case study, a questionnaire was developed by the researcher consisting of (52) items, and distributed among seven dimensions. The study population consisted of all employees in Jordan Customs Department totaling around (3466) male and female employees, while the study sample was (215) elements representing (6.2%) of the population. The researcher then collected the data and used SPSS for analysis.The most important result of the study is as follows:• There is a positive and significant statistical impact at the level of significance (α≤0.05) of managerial communications dimensions (comm. directions, comm. Tools, comm. skills, and comm. obstacles) on organizational change management dimensions (individual, group, and systems perspectives).• The level of managerial communications dimensions is high (4.04) on 5-Likert scale.• The level organizational change management dimensions is high (4.04) on 5-Likert scaleWhile the study came up with the following key recommendation:• To support and widespread the culture of change among all employees of Jordan Customs Department, and to convince them about the importance of change and attract their initiatives and participation.
Keywords: administrative communication; organizational change management; Jordanian Customs Department